Comparison of Eco-Mse and Pst-Mse Primer Combinations in Generating AFLP Map of Tomato - Ojha, BR (Journal of the Institute of Agriculture and Animal Science, 2005)
An experiment was conducted at Wageningen University and Research Centre (WUR), Unifarm, Haarweg, Wageningen, The Netherlands in 2000 to compare Eco-Mse and Pst-Mse primer combinations to generate AFLP markers of tomato. Back cross first (BC1) population ofLycopersicon esculentum cv money maker and Lycopersicon pennellii LA716 was used. Six primer combinations (three of Eco-Mse and three of Pst-Mse) were used. A total of 122 AFLP markers were found generating 76 markers by Eco-Mse primer combination and 46 markers by Pst-Mse primer combination. The average number of informative markers per primer combination was 20.33 ranging from 11 (P11M50) to 36 (E35M48). Similarly the average number of informative markers per chromosome was 10.16 ranging from 4 (chromosome number 8) to 16 (chromosome number 1). Within Eco-Mse primer combinations, E32M50 generated the least (18) and E35M48 generated the highest (36) AFLP markers. Similarly, within Pst-Mse primer combination, P14M50 generated the highest (20) and P11M50 generated the least (11) AFLP markers. The Eco-Mse primer combination generated the highest number of marker (12) in chromosome 9 and the lowest (2) in chromosome number 8. Similarly, the Pst-Mse primer combination generated the highest number of markers (9) in chromosome number 1 and the lowest (2) in chromosome number 3, 8, 11 and 12. The AFLP map spanned 843 cM. The longest AFLP map was found in chromosome 1 and spanned 98 cM and the shortest in chromosome 8 and spanned 46 cM. Key words: Tomato, Back cross, Primer combination, AFLP map J. Inst. Agric. Anim. Sci. 26:27-35 (2005)